Korelasi Penegakkan Etika Pancasila Dalam Mengatasi Kasus Kekerasan Seksual Di Kampus - Hanifah Miftahul Jannah; Insani Nurul Qolbi; Naila Nabila Fuadi; Maulia Depriya Kembara (International Forum of Researchers and Lecturers, 2023)
Sexual violence in campus settings has become an increasingly concerning issue in Indonesia. From the perspective of Pancasila as an ethical system, sexual violence is an action that contradicts the noble values of the Indonesian nation. Campuses should be a safe and comfortable environment for everyone, especially students, but the reality is that there are still many cases of sexual violence occurring within them. The purpose of this article is to discuss sexual violence in campus settings from the perspective of Pancasila as an ethical system. The method used is a qualitative approach by conducting a literature review related to sexual violence in campus settings and the values of Pancasila. The results show that sexual violence is an action that contradicts the values of Pancasila, such as social justice, fair and humane treatment, and mutual cooperation. Therefore, efforts to prevent and address sexual violence in campus settings must prioritize these Pancasila values. Some efforts that can be taken include raising awareness among students and campus staff about sexual violence, promoting a culture that values diversity and strengthens solidarity between students and campus staff, and improving the effectiveness of legal action against perpetrators of sexual violence. Thus, it is hoped that a safe, comfortable, and human rights-respecting campus environment can be created.